Children’s Exploration of Their Surrogacy Origins in Gay Two-Father Families: Longitudinal Associations With Child Attachment Security and Parental Scaffolding During Discussions About Conception - Carone, Nicola; Barone, Lavinia; Manzi, Demetria; Baiocco, Roberto; Lingiardi, Vittorio; Kerns, Kathryn (Frontiers in Psychology, 2020)
Evidence is lacking about the factors that are pivotal in enhancing the exploration of surrogacy origins in children of gay fathers during middle childhood. The present study examined the separate and combined influences of child attachment security and parental scaffolding (i.e., fathers’ attempts to accept, encourage, and emotionally support their children’s expression of thoughts and feelings) during discussions about conception on children’s exploration of their surrogacy origins in 30 Italian children born to gay fathers through gestational surrogacy. Within each family, both father–child dyads (n = 60) participated in a 5-minute videotaped conversation regarding an aspect of the child’s conception when children were mean aged 8.3 years (t1). At this time, children were also administered the Security Scale to evaluate their attachment security. Approximately 18 months later (t2; Mage = 9.9 years), children were interviewed about their surrogacy origins. Linear mixed models (LMMs) for longitudinal data indicated that, with higher levels of parental scaffolding, only children who perceived greater attachment security reported greater exploration of their surrogacy origins. The findings are the first to underscore the importance of conversations about surrogacy within the context of parent–child attachment relationships, as well as the importance of fathers sensitively supporting their children as they explore their origins during middle childhood. In doing so, it is expected that fathers will likely facilitate their children’s positive integration of their surrogacy conception into a coherent sense of identity during adolescence.